Alleviation of nutrient co‐limitation induces regime shifts in post‐fire community composition and productivity in Arctic tundra - Klupar, Ian; Rocha, Adrian V.; Rastetter, Edward B. (Global change biology, 2021)
Recent unprecedented fires in the Arctic during the past two decades have indicated a pressing need to understand the long‐term ecological impacts of fire in this biome. Anecdotal evidence suggests that tundra fires can induce regime shifts that change tussock tundra to more shrub‐dominated ecosystems. However, the ecological mechanisms regulating these shifts are poorly understood, but are hypothesized to involve changes to nutrient availability in this nutrient limited system. Here we conducted a 4‐year two‐factorial (control: C, nitrogen along: N+, phosphorus alone: P+, nitrogen and phosphorus combined: NP+) fertilization experiment in both unburned and burned tundra to test this hypothesis after a decade of post‐fire recovery. A decade after fire, the burned site exhibited an increase in soil nitrogen and phosphorus availability and a transition toward taller, more productive, and more deciduous vegetation. This shift in vegetation structure, composition, and function was induced at the unburned site through the addition of both NP+ and the alleviation of their co‐limitation. Both burned and unburned tundra responded similarly to fertilizer treatments by increasing leaf area index, greenness, and canopy height in NP+ treatments, and exhibited no significant response in individual N+ or P+ treatments. These results point to a greater need to understand coupled carbon, nitrogen, and phosphorus cycles in this system, and suggest that post‐fire regime shifts are regulated by the alleviation of nitrogen and phosphorus co‐limitation in Arctic tundra. Post‐fire regime shifts in tundra vegetation community composition were induced by the addition of nitrogen and phosphorus at an unburned site.